Carajurin Induces Apoptosis in Leishmania amazonensis Promastigotes through Reactive Oxygen Species Production and Mitochondrial Dysfunction - João Victor Silva-Silva; Carla J. Moragas-Tellis; Maria S. S. Chagas; Paulo Victor R. Souza; Davyson L. Moreira; Daiana J. Hardoim; Noemi N. Taniwaki; Vanessa F. A. Costa; Alvaro L. Bertho; Daniela Brondani; Eduardo Zapp; Aldo Sena de Oliveira; et al. (MDPI AG, 2022)
Carajurin is the main constituent of Arrabidaea chica species with reported anti-Leishmania activity. However, its mechanism of action has not been described. This study investigated the mechanisms of action of carajurin against promastigote forms of Leishmania amazonensis. Carajurin was effective against promastigotes with IC50 of 7.96 ± 1.23 μg.mL−1 (26.4 µM), and the cytotoxic concentration for peritoneal macrophages was 258.2 ± 1.20 μg.mL−1 (856.9 µM) after 24 h of treatment. Ultrastructural evaluation highlighted pronounced swelling of the kinetoplast with loss of electron-density in L. amazonensis promastigotes induced by carajurin treatment. It was observed that carajurin leads to a decrease in the mitochondrial membrane potential (p = 0.0286), an increase in reactive oxygen species production (p = 0.0286), and cell death by late apoptosis (p = 0.0095) in parasites. Pretreatment with the antioxidant NAC prevented ROS production and significantly reduced carajurin-induced cell death. The electrochemical and density functional theory (DFT) data contributed to support the molecular mechanism of action of carajurin associated with the ROS generation, for which it is possible to observe a correlation between the LUMO energy and the electroactivity of carajurin in the presence of molecular oxygen. All these results suggest that carajurin targets the mitochondria in L. amazonensis. In addition, when assessed for its drug-likeness, carajurin follows Lipinski''s rule of five, and the Ghose, Veber, Egan, and Muegge criteria.